Original articleNeuroprotective properties of ciliary neurotrophic factor on retinoic acid (RA)-predifferentiated SH-SY5Y neuroblastoma cells - Wang, Ke; Zhou, Fanfan; Zhu, Xue; Zhang, Kai; Huang, Biao; Zhu, Lan; Zhu, Ling (Folia Neuropathologica, 2014)
Ciliary neurotrophic factor (CNTF) is a neurocytokine, which could promote survival and/or differentiation in many cell types. In this study, the biological effects of CNTF on retinoic acid (RA)-predifferentiated SH-SY5Y neuroblastoma cells and the underlying molecular mechanism of this effect were investigated for the first time. The results showed that RA was able to increase cells susceptibility to CNTF via regulating the expression levels of CNTF receptors. A further study revealed that CNTF could induce phosphorylation of STAT3, Akt and ERK1/2 in RA-predifferentiated SH-SY5Y neuroblastoma cells, while the promoting activity of CNTF on survival and neurite growth of cells was attenuated by co-treatment with JAK2 inhibitor AG490 (25 M), STAT3 inhibitor Curcumin (50 M), PI3K inhibitor LY-294002 (50 µM), but not by co-treatment with MEK inhibitor PD98059 (50 M). These findings suggested that JAK2/STAT3, as well as PI3K/Akt, play important roles in mediating the survival and neurite growth response of RA-predifferentiated cells to CNTF. Our study may be useful to further understand the functional role of CNTF and offer a convenient model to explore the therapeutic potential of CNTF in neurodegenerative diseases.